Usage of Blockchain to Ensure Audit Data Integrity - Wibowo, Tony; Christian, Yefta (Department of Accounting, Faculty of Economics and Business, Universitas Pembangunan Nasional Veteran Jakarta, 2021)
Usage of technology to help finance audit process is not a new instance. But since the rise of 4th industrial revolution and emergence of smart technology relatively in a short period of time, adopting technology have its challenges and drawbacks. Data Integrity has been an issue for finance audit process because digital data is easy to tamper. This condition makes audit process become difficult and potential of audit fraud is high. In this study we would like to explore usage blockchain technology as future database engine for AIS. Blockchain as a technology relatively unheard before cryptocurrency albeit its advanced technology in data storage to ensure data integrity. We will explore the advantages and risk in adopting blockchain as well as current state of academics and technology regarding blockchain adoption.